Value of Preoperative Systemic Immune-Inflammation Index and Albumin-Bilirubin Grade in Patients with Hepatocellular Carcinoma Undergoing Transarterial Embolization - Fushuang Ha; Fushuang Ha; Fushuang Ha; Fushuang Ha; Xue Wang; Xue Wang; Xue Wang; Xue Wang; Tao Han; Kefeng Jia; Sen Wang; Dezhao Song (Turkish Journal of Gastroenterology, 2023)
Background: The systemic immune-inflammation index reflects the systematic inflammatory status, and the albumin-bilirubin grade reflects the liver function. In patients with hepatocellular carcinoma receiving transarterial chemoembolization, their combined clinical utility has not been fully explored. Herein, we purposed to determine the prognostic worthiness of systemic immune-inflammation index –albumin-bilirubin scores in patients receiving transarterial chemoembolization for unresectable hepatocellular carcinoma.Methods: Patients who were treated with transarterial chemoembolization after being diagnosed with hepatocellular carcinoma between 2008 and 2016 were recruited for this research work. Systemic immune-inflammation index and albumin-bilirubin scores were determined prior to treatment. The clinico-pathological factors related to overall survival were determined via univariate along with multivariate analyses.Results: A total of 295 patients were retrospectively studied. Patients with systemic immune-inflammation index–albumin-bilirubin score of 2 had the worst outcomes, exhibiting a median overall survival of 11 months (95% CI, 8.44-13.56 months) in contrast with subjects in the systemic immune-inflammation index–albumin-bilirubin 1 group (median OS, 26 months; 95% CI, 21.25-30.75 months) and the systemic immune-inflammation index–albumin-bilirubin 0 class (median OS, 31 months; 95% CI, 12.76-49.24 months). The 1-, 3-, and 5-year rates of survival were 45.3%, 1.3%, and 0% for patients in the systemic immune-inflammation index–albumin-bilirubin 2 category; 76.4%, 35.0%, and 14.6% for those in the systemic immune-inflammation index–albumin-bilirubin 1 category; and 85.6%, 46.7%, and 35.0% for those in the systemic immune-inflammation index–albumin-bilirubin 0 category, respectively (P < .001).Conclusions: The systemic immune-inflammation index–albumin-bilirubin score could be a simple indicator to estimate the prognosis in individuals with hepatocellular carcinoma being treated with transarterial chemoembolization. Patients in the systemic immuneinflammation index–albumin-bilirubin 2 category were more likely to be related to a shorter overall survival.Cite this article as: Ha F, Wang X, Han T, Jia K, Wang S, Song D. Value of preoperative systemic immune-inflammation index and albumin-bilirubin grade in patients with hepatocellular carcinoma undergoing transarterial embolization. Turk J Gastroenterol. 2023;34(4):413-420.